Golden Bear to be Friend Ship - Vallejo News Chronicle (Vallejo News Chronicle)
The California Maritime Academy will convert its annual training cruise this year into a friendship trip to Italy, Greece and France, according to an announcement made today in Sacramento by Governor Earl Warren. The Golden Bear, training ship of the Academy, will carry 1,500 tons of relief supplies BUch as food and clothing contributed by the people of the state.